Antidepressant use and risk of suicide and attempted suicide or self harm in people aged 20 to 64: cohort study using a primary care database - Coupland, Carol; Hill, Trevor; Morriss, Richard; Arthur, Antony; Moore, Michael; Hippisley-Cox, Julia (British Medical Association, 2015)
Objective